MENINGKATKAN HASIL BELAJAR IPA MELALUI MODEL PROBLEM BASED LEARNING (PBL) PADA SISWA KELAS VIII SMPS DIAN TODAHE HALMAHERA BARAT - MILSAN SABAN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This study aims to improve science learning outcomes through a problem-based learning model for class VIII students at SMPS Diant Todahe West Halmahera. This research is a type of Classroom Action Research (CAR). This research will be carried out at SMPS Dian Todahe West Halmahera. Data collection techniques from this study using test results and observation results. Based on the results of Classroom Action Research (PTK) conducted in two cycles in Natural Sciences (IPA) subjects on style material, it can be concluded that the Problem Based Learning (PBL) model can improve science learning outcomes on style material in class VIII students of SMPS Dian Todahe West Halmahera Regency. The increase in science learning outcomes is known by the test results in Cycle I and Cycle II which show an increase in the average score and percentage of classical completeness. In this study, referring to indicators of success, the value calculated is the percentage of classical completeness if student learning outcomes ? 85% of the total number of students in one class get a score of ? 60. The average value of style material students in the initial conditions (pre-cycle) is 50 with classical completeness of 40% (2 students) of 12 students who scored ? 60 (KKM score). Cycle I was 61 with classical completeness of 60% (4 students) who scored ? 60 (KKM score). Cycle II of 8 with classical completeness of 80% (8 students) who achieved a score of ? 60 (KKM score). Thus, according to the indicators of success, the Classroom Action Research (CAR) through the Problem Based Learning (PBL) model of style material in class VIII students of SMPS Dian Todahe West Halmahera was declared successful. ABSTRAKPenelitian ini bertujuan untuk meningkatkan hasil belajar IPA melalui model problem based learning pada siswa kelas VIII SMPS Diant Todahe Halmahera Barat. Penelitian ini termasuk jenis Penelitian Tindakan Kelas (PTK). Penelitian ini akan dilaksanakan di SMPS Dian Todahe Halmahera Barat. Teknik pengumpulan data dari penelitian ini menggunakan hasil tes dan hasil observasi. Berdasarkan hasil Penelitian Tindakan Kelas (PTK) yang dilaksanakan sebanyak dua siklus pada mata pelajaran Ilmu Pengetahuan Alam (IPA) pada materi gaya, dapat disimpulkan bahwa model Problem Based Learning (PBL) dapat meningkatkan hasil belajar IPA materi gaya pada siswa kelas VIII SMPS Dian Todahe Kab.Halmahera Barat. Peningkatan hasil belajar IPA diketahui dengan hasil tes pada Siklus I dan Siklus II yang menunjukkan peningkatan nilai rata- rata dan persentase ketuntasan secara klasikal. Di dalam penelitian ini merujuk pada indikator keberhasilan, nilai yang dihitung yaitu persentase ketuntasan klasikal apabila hasil belajar siswa ? 85% dari jumlah total siswa dalam satu kelas mendapatkan nilai ? 60. Rata- rata nilai siswa materi gaya pada kondisi awal (prasiklus) 50 dengan ketuntasan klasikal sebesar 40% (2 siswa) dari 12 siswa yang mencapai nilai ? 60 (nilai KKM). Siklus I sebesar 61 dengan ketuntasan klasikal sebesar 60% (4 siswa) yang mencapai nilai ? 60 (nilai KKM). Siklus II sebesar 8 dengan ketuntasan klasikal 80% (8 siswa) yang mencapai nilai ? 60 (nilai KKM). Dengan demikian, sesuai dengan indikator keberhasilan maka Penelitian Tindakan Kelas (PTK) melalui model Problem Based Learning (PBL) materi gaya pada siswa kelas VIII SMPS Dian Todahe Halmahera Barat dinyatakan berhasil.